The trade-offs of emotional reactivity for youths' social information processing in the context of maternal depression - Flynn, Megan; Rudolph, Karen D. (Frontiers in Integrative Neuroscience, 2012)
Although research demonstrates that emotional experiences can influence cognitive processing, little is known about individual differences in this association, particularly in youth. The present study examined how the emotional backdrop of the caregiving environment, as reflected in exposure to maternal depression and anxiety, was linked to biases in youths’ cognitive processing of mother-referent information. Further, we investigated whether this association differed according to variation in youths’ emotional reactivity to stress. Youth (50 boys, 46 girls; M age = 12.36, SD = 1.05) completed a behavioral task assessing cognitive bias. Semi-structured interviews were administered to assess (a) youths’ emotional reactivity to naturally occurring stressors, and (b) maternal depression and anxiety. Hierarchical multiple regression analyses revealed that emotional reactivity to interpersonal stressors moderated the linkage between maternal depression and cognitive bias such that maternal depression predicted a greater negative bias in youth exhibiting high and average, but not low, levels of emotional reactivity. At low levels of maternal depression, youth with heightened interpersonal emotional reactivity showed a greater positive cognitive bias. This pattern of effects was specific to interpersonal (but not noninterpersonal) emotional reactivity and to maternal depression (but not anxiety). These findings illuminate one personal characteristic of youth that moderates emotion-cognition linkages, and reveal that emotional reactivity both enhances and impairs youths’ cognitive processing as a function of socialization context.